TEACHING A FOREIGN LANGUAGE IN PRESCHOOL AND PRIMARY EDUCATION - Nazarova Ma’rifat Abduraim qizi; Jumanazarov Umid (Journals Park Publishing, 2023)
A foreign language as one of the means of cognition and communication with the outside world occupies a special place in the modern education system due to its social, cognitive and developmental functions. This article is based on the teaching of a foreign language in preschool and primary education.
Keywords: preschool ,educational ,primary education, upbringing,cognition of the world,communication.